(untitled) (Raparin Journal of Humanities (RJH), 2023)
The term genre in the literary literature means (type, style, category, or literary element). genres include all the artistic frameworks and templates that poets and writers use to shape their thoughts, consciousness and emotions. In ancient times (classical age) the boundaries between literary genres are clearly defined on the basis of the purity of genres. In general, genres had enjoyed a kind of independence. However, in the later stages, the boundaries between genres were crossed since they merged, went into each other and lost their sanctity and independence. For example, a genre of epic or free verse poetry is a combination of the characteristics of two or more genres within one new literary genre. In addition, the four main genres of poetry, lyric, epic, drama, didactic form the general structure of the base of poetry, each of which has several different genres. This feature, of course, existed in the most publications of the ’Kurdistan Newspaper’ in Tehran.